VALIDATION OF A DIETARY INTAKE TOOL FOR AFRICAN‐AMERICAN DIALYSIS PATIENTS WITH LOW LITERACY. Issue 2 (6th December 2014) - Duffrin, Christopher; Carraway‐Stage, Virginia G.; Briley, Alexis; Christiano, Cynthia
SUMMARY Background This study analysed the validity and reliability of a food frequency questionnaire designed for African‐American patients with low literacy. This instrument was designed specifically to meet the need for a tool that was short, easy to understand, and met clinical reliability and validity standards. Objectives Assessing patient nutritional status and dietary intake is crucial to the care of patients in end stage kidney disease. The development of a quick and reliable nutritional assessment tool for patients with low literacy could increase nutritional counselling effectiveness and improve patient outcomes. Design The renal food frequency questionnaire (RFF) and a standard 24‐hour recall were administered to a general population of African‐American patients undergoing dialysis. Registered Dieticians and statistical analyses were used to validate the content and structural validity and reliability of the RFF to adequately measure dietary intake. Participants The study sample consisted of 30 African‐American patients who received dialysis treatment at a regional teaching hospital facility. Results The RFF was found to be a simple, easy to understand instrument with low reading complexity (grade level 4.4). Inter‐rater reliability was found to be high (.81–1.00), and statistical analysis determined a high level of clinical validity. Conclusion The RFF was found to be a valid dietary recall tool that is appropriate for patients with limited literacy. It was found to have acceptable reliability and validity when compared with a standard 24‐hour recall and has potential for use as a dietary intake and monitoring tool in patients undergoing dialysis.